Accompagner la réorientation en licence : une évaluation de l’implantation d’un dispositif d’aide à la réussite - Nathalie Younès; Juliette Robert; Elisa Guyon; Emmanuèle Auriac-Slusarczyk (Éducation et Socialisation)
The article deals with the difficult question of the program evaluation to help students achieve their Bachelor's degree by an in-depth study, at the UCA, of the target public of a program intended to accompany some students in their (re)orientation by cross-referencing the results of two surveys. The first, conducted among undergraduate students, shows that they do not differ significantly in their potential need to be support in their (re)orientation, depending on whether they have been labelled “yes” or “yes, if” on Parcoursup. The second shows that language proficiency is a salient factor in characterising, by default, the students followed qualitatively and that the experienced sections, Law, AES, Economics, Management, do not have the same attendance rates. Questions arise in order to adjust the program to the reality of the public and to choose more appropriate and less segregated selection methods.